COVID-19, students satisfaction about e-learning and academic achievement: Mediating analysis of online influencing factors - Younas, Muhammad; Noor, Uzma; Zhou, Xiaoyong; Menhas, Rashid; Qingyu, Xu (Frontiers in Psychology, 2022)
Background: The current study examines the student satisfaction about E-learning, the adaption of online learning channels, digital competency of students' involvement and academic achievement during COVID-19. Purpose: The study purpose is to examine the online influencing components for learning among the university students in Pakistan during the COVID-19 Pandemic. Methods: The study population comprised Pakistani university students in Punjab province who took online lessons throughout the epidemic. In accordance with the study's purpose, a questionnaire survey was employed to gather primary data. SPSS-23 used for analyzing the demographic data, and clean and prepare data for testing hypotheses. Smart-PLS 3.0 was used to investigate the suggested study framework using structural equation modeling (SEM). Results: The analysis of SEM model shows that all planned hypotheses (Adaptation of Online Education Channels -> Satisfaction about E-learning, COVID-19 Pandemic -> Adaptation of Online Education Channels, COVID-19 Pandemic -> Digital Competence, COVID-19 Pandemic -> Motivation for Online Learning, COVID-19 Pandemic -> Willingness for Online Learning, Digital Competence -> Satisfaction about E-learning, Motivation for Online Learning -> Satisfaction about E-learning, Satisfaction about E-learning -> Academic Achievement, Willingness for Online Learning -> Satisfaction about E-learning) are confirmed. Conclusion: The results linked E-learning satisfaction to academic success and Pakistani students who utilized E-learning throughout the outbreak reported higher levels of academic satisfaction and achievement.